On the solutions of nonlinear second order differential equation with finite delay - Tidke, Haribhau Laxman (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
The main aim of this paper is to study the approximate solutions, uniqueness and other properties of solutions of nonlinear second order differential equation with given initial values. A variant of the well known Gronwall-Bellman integral inequality with explicit estimate is used to establish the results.